Carbon nanotube-supported Ni–CeO2 catalysts. Effect of the support on the catalytic performance in the low-temperature WGS reaction. (May 2016) - Dongil, A.B.; Pastor-Pérez, L.; Escalona, N.; Sepúlveda-Escribano, A.
Abstract: The low temperature water-gas shift (WGS) reaction has been studied over two commercial multiwall carbon nanotubes-supported nickel catalysts promoted by ceria. For comparison purposes, activated carbon-supported catalysts have also been studied. The catalytic performance and the characterization by N2 adsorption analysis, powder X-ray diffraction (XRD), temperature-programmed reduction with H2 (TPR-H2 ), X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy (TEM) analysis showed that the surface chemistry has an important effect on the dispersion of ceria. As a result, ceria was successfully dispersed over the carbon nanotubes (CNTs) with less graphitic character, and the catalyst afforded better activity in WGS than the catalyst prepared over massive ceria. Moreover, a 20 wt.% CeO2 loading over this support was more active than the analogous catalyst with a 40 wt.% loading. The ceria nanoparticles were smaller when the support was previously oxidized, however this resulted in a decrease of the activity.